WARSHIP BUILDERS: AN INDUSTRIAL HISTORY OF U.S. NAVAL SHIPBUILDING, 1922-1945 - Heinrich, Thomas R., 1963- (Studies in Naval History and Sea Power, 2020)
"Warship Builders is the first scholarly study of the U.S. naval shipbuilding industry from the early 1920s to the end of World War II, when American shipyards produced the world's largest fleet that helped defeat the Axis powers in all corners of the globe. A colossal endeavor that absorbed billions and employed virtual armies of skilled workers, naval construction mobilized the nation's leading industrial enterprises in the shipbuilding, engineering, and steel industries to deliver warships whose technical complexity dwarfed that of any other weapons platform"--